Identification and validation of hub gene TNFAIP6 of fibroblast-like synoviocytes in rheumatoid arthritis - LEI Lei; LYU Yuxin; ZHANG Jing (陆军军医大学学报)
Objective‍　‍To identify the hub gene of fibroblast-like synoviocytes in rheumatoid arthritis (RA) and verify its impact on proliferation, migration and invasion of the cells. Methods‍　‍Four independent synovial tissue microarray transcriptome sequencing datasets and one single cell sequencing dataset were downloaded from the Gene Expression Omnibus (GEO) database, and the hub gene of RA fibroblast-like synovial cells was identified by differential gene analysis, weighted gene co-expression network analysis (WGCNA) and single-cell sequencing data analysis. The expression of TNFAIP6 in human RA fibroblast-like synovial cell line MH7A was detected by RT-qPCR and Western blotting under simulated inflammatory environment. After MH7A cells were transfected with si-TNFAIP6, CCK-8 and Transwell assays were applied to detect the effects of silencing TNFAIP6 on the proliferation, migration and invasion abilities of MH7A cells. Results‍　‍With the aid of differential gene expression analysis, WGCNA, and single-cell sequencing data, we identified TNFAIP6 as the characteristic gene of RA fibroblast-like synoviocytes. RT-qPCR and Western blot assay demonstrated that TNFAIP6 was significantly highly expressed at mRNA and protein levels in MH7A cells stimulated with 10 ng/mL TNF-α when compared to the cells treated with PBS (P<0.05). CCK-8 and Transwell assays indicated that the silencing of TNFAIP6 markedly inhibited the proliferation, migration and invasion abilities of MH7A cells when compared with the control cells (FAM-si-NC,P<0.05). Conclusion‍　‍TNFAIP6 is highly expressed specifically in RA fibroblast synoviocytes, which promotes the proliferation, migration and invasion, and may be the main contributor to the abnormal activation of RA fibroblast synoviocytes.